Eyes and balls: from sexuality to historicity in history of the eye - Sobral, Luís Felipe (2021)
Bataille under a pseudonym in 1928, offers several elements to the debate on sexuality, its norms, transgressions and transformations. However, this article seeks to demonstrate that the sexuality in the book is tied to a very specific notion of historicity, produced by the literary innovations of the interwar years. Based on an analysis of the episode of the fatal accident suffered by the matador Manuel Granero, the article follows not only the writing of the novella, but also the path of psychoanalytical deciphering taken by Bataille, leading to a historical perspective far beyond the realm of desire and fantasy.